Analysis of Corporate Entrepreneurship in Public R&D Institutions - Alexandru Agapie (Sustainability, 2018)
This paper aimed at establishing a Corporate Entrepreneurship diagnosis model within public R&D institutions. We based our analysis on empirical identification of a generalized set of organizational factors, perceived as intrapreneurship vectors. The quantitative research targeted 50 experienced public entities and was based on validating one of the most popular psychometric instruments in the entrepreneurial literature: the Corporate Entrepreneurship Assessment Instrument (CEAI)—originally intended for the North American economic environment. As recent literature questioned the cross-cultural portability of psychometric instruments, this study intended to validate the five-factor intrinsic structure of CEAI. The five factors deduced by our statistical analysis were: support for opportunity investigations and reinforcement; dynamic environment and recognition; decreased formalization; knowledge sharing; time availability and strategic awareness. Next, the factor scores were used as input variables for a logistic regression procedure, with the output variable being the intrapreneurial value of the respondents’ institutions. Two factors contribute considerably to the predicted intrapreneurial value: support for opportunity investigations and reinforcement and decreased formalization. The validity of the whole approach is supported by the relevance of the original CEAI questionnaire, able to reveal intrapreneurial characteristics, and by the prediction power of the logistic regression model over the intrapreneurial propensity of public institutions.